Brown fat organogenesis and maintenance requires AKT1 and AKT2 - Joan Sanchez-Gurmaches; Camila Martinez Calejman; Su Myung Jung; Huawei Li; David A. Guertin (Elsevier, 2019)
Objective: Understanding the signaling mechanisms that control brown adipose tissue (BAT) development is relevant to understanding energy homeostasis and obesity. The AKT kinases are insulin effectors with critical in vivo functions in adipocytes; however, their role in adipocyte development remains poorly understood. The goal of this study was to investigate AKT function in BAT development. Methods: We conditionally deleted Akt1 and Akt2 either individually or together with Myf5-Cre, which targets early mesenchymal precursors that give rise to brown adipocytes. Because Myf5-Cre also targets skeletal muscle and some white adipocyte lineages, comparisons were made between AKT function in BAT versus white adipose tissue (WAT) and muscle development. We also deleted both Akt1 and Akt2 in mature brown adipocytes with Ucp1-Cre or Ucp1-CreER to investigate AKT1/2 signaling in BAT maintenance. Results: AKT1 and AKT2 are individually dispensable in Myf5-Cre lineages in vivo for establishing brown and white adipocyte precursor cell pools and for their ability to differentiate (i.e. induce PPARγ). AKT1 and AKT2 are also dispensable for skeletal muscle development, and AKT3 does not compensate in either the adipocyte or muscle lineages. In contrast, AKT2 is required for adipocyte lipid filling and efficient downstream AKT substrate phosphorylation. Mice in which both Akt1 and Akt2 are deleted with Myf5-Cre lack BAT but have normal muscle mass, and doubly deleting Akt1 and Akt2 in mature brown adipocytes, either congenitally (with Ucp1-Cre), or inducibly in older mice (with Ucp1-CreER), also ablates BAT. Mechanistically, AKT signaling promotes adipogenesis in part by stimulating ChREBP activity. Conclusions: AKT signaling is required in vivo for BAT development but dispensable for skeletal muscle development. AKT1 and AKT2 have both overlapping and distinct functions in BAT development with AKT2 being the most critical individual isoform. AKT1 and AKT2 also have distinct and complementary functions in BAT maintenance. Keywords: Brown adipose tissue, White adipose tissue, Development, Adipogenesis, Insulin signaling, AKT, mTORC2, Obesity, Lipodystrophy